Cobas 4800 HPV detection in the cervical, vaginal and urine samples of women with high-grade CIN before and after treatment. Issue 7 (15th April 2015) - Stanczuk, Grazyna A; Currie, Heather; Baxter, Gwen; Foster, Adele; Gibson, Lindsay; Graham, Catriona; Cuschieri, Kate
Abstract : Aims: To assess the performance of a clinically validated human papillomavirus (HPV) test (the Cobas 4800 HPV test) in urine and self-taken vaginal specimens within a colposcopy population and to assess HPV prevalence before and after treatment across the different biospecimens. Methods: A total of 100 women attending a colposcopy clinic provided three biospecimens (a clinician-taken liquid-based cytology sample (LBC), a self-taken vaginal sample and a urine sample) for HPV testing. HPV prevalence and concordance was compared across the biospecimens and clinical performance relative to the detection of cervical intraepithelial neoplasia (CIN)2+ and CIN3+ was assessed. A total of 39 women retuned at 6 months for a post-treatment follow-up appointment, and HPV concordance in all biospecimens was measured relative to their original HPV status. Results: 65 cases of CIN2+ were detected in the baseline population; sensitivity for CIN2+ was 92% (82 to 97) for the vaginal and the LBC sample and 80.0 (68% to 88%) for the urine sample. In the follow-up (post treatment) population, women were twice as likely to be HPV positive in their urine or vaginal sample compared with the equivalent LBC sample. Conclusions: Vaginal and LBC samples showed very similar performance for the detection of CIN2+ in this population using the Cobas HPV test; further validation of these findings in screening contexts will be of value. Self-taken samples may have less utility in a 'test of cure' setting—given the higher prevalence of HPV relative to LBC.